2018
DOI: 10.1140/epjp/i2018-12113-0
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement negativity for adjacent subsystems in AdSd+1/CFTd

Abstract: We establish our recently proposed holographic entanglement negativity conjecturefor mixed states of adjacent subsystems in conformal field theories with concrete higher dimensional examples. In this context we compute the holographic entanglement negativity for mixed states of adjacent subsystems in d-dimensional conformal field theories dual to bulk AdS d+1 vacuum and AdS d+1 -Schwarzschild black holes. These representative examples provide strong indication for the universality of our conjecture which affir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…A higher dimensional extension of the above conjecture for the mixed state of adjacent subsystems in a holographic CF T d was proposed subsequently in [32]. As earlier this involved a specific algebraic sum of the areas of co-dimension two bulk static minimal surfaces anchored on the respective subsystems in the dual CF T d .…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…A higher dimensional extension of the above conjecture for the mixed state of adjacent subsystems in a holographic CF T d was proposed subsequently in [32]. As earlier this involved a specific algebraic sum of the areas of co-dimension two bulk static minimal surfaces anchored on the respective subsystems in the dual CF T d .…”
Section: Introductionmentioning
confidence: 92%
“…In this section we briefly review the holographic entanglement negativity conjecture for a bipartite mixed state configuration of adjacent subsystems in dual CF T s. To this end we first describe the holographic entanglement negativity conjecture for the mixed state configuration above in the context of the AdS 3 /CF T 2 scenario [29]. Following this we briefly discuss the extension of our conjecture to a generic higher dimensional AdS d+1 /CF T d scenario [32].…”
Section: Holographic Entanglement Negativity Conjecturementioning
confidence: 99%
See 2 more Smart Citations
“…We plan to return to these interesting questions in the future. Let us remark that in [9][10][11] it was suggested that in holographic framework the mutual information, multiplied by a constant, could be a dual to the entanglement negativity E. This was revised by a suggestion [14] that the entanglement wedge cross section E W , supplemented by the backreaction of the hanging minimal (cosmological) surfaces to the geometry, is actually a gravity dual of entanglement negativity. While lots of important work [4,6,7, has been carried out and most obvious inequalities tested, we feel that it is premature to identify E W one way or the other.…”
Section: Introductionmentioning
confidence: 99%